Consumer Willingness to Pay for Food Safety Attributes in China: A Meta-Analysis. Issue 2 (15th March 2021) - Yang, Wei; Fang, Lan
Abstract: Food safety incidents in China have led to increased research into consumers' willingness to pay (WTP) for food safety attributes. This paper employed meta-regression models to analyze the empirical results of WTP estimates for safety attributes through a thorough literature retrieval of relevant studies. The results showed that, to varying degrees of significance, consumer WTP varied across different study characteristics. Regarding types of food products, dairy products were found to be associated with the highest WTP, followed by pork and crop. In addition, WTP estimates of attributes directly related to health benefits were higher than those with mixed benefits. A significantly positive time effect was found on WTP, with an increasing trend of WTP after the San Lu powder scandal in 2008. Knowing that WTP estimates are sensitive to a number of characteristics, the study provides additional insights into understanding market response to food safety attributes in China.